Les sceaux des abbés et du convent de la Trinité de Fécamp, XIIe-début du XIVe siècle - Michaël Bloche (Tabularia)
The seals of the Abbots and the convent of the Trinity of Fécamp, interesting from many points of view, in particular certain "contre-sceaux" derived from reused engraved gemstones from antiquity, have never been the subject of any long term study. A corpus has been compiled, while limited (12 originals applied seals), no matrices survive and seals with lacuna for certain Abbots, enough however survive to provide an introduction to Fécamp sigillography since the 12th to the beginning of the 14th centuries to be made. This study comprises a description of the different types seal that have survived as well as a study of the corroboration, the sealing practices, and the connections between the seals and the superscription.